Penggunaan Teknik Storytelling dalam Keterampilan Menyajikan Cerita Sejarah di SMA Negeri 3 Painan - Reren Febyusri; Zafri Zafri (Jurusan Sejarah FIS UNP, 2019)
This research aims to find out the picturization of student skills on verbally presenting story of history by using storytelling technics. This research processed by the descriptive quantitative data to picturised the condition based on field data. The subject of this research were 22 students of XI social class in Senior High school 3 Painan. Research instrument in the form of skill assessment rubric using rating scale, and data processing were statistic deskriptive. The result of the research of student skills on verbally presenting story of history by using storytelling technics in Senior High School 3 Painan are : (1) storytelling is usefull on learning history comprehension that are fact, concept, causality, and contiunity of history; 2) storytelling accomodate student oral skill and student ability to create a story that represent the event of history; and (3) storytelling need a long prepared time too make sure student readiness to telling the story. It is because student should do a lot of thing to create the story, the material of story and also their readiness to perform.